Indian Pesticide Industry: A Marketing Perspective - Chand, Subhash; Narwal, Mahabir (Gyan Management Journal, 2009)
Thi.s paper examines lhe marketing-mix strategies of different pesticide companies. Primary data :pect to same was collected from sample of 97 pesticide cor,tpanies through random selection method. observed that the Indian pesticide industry is highly competitive due lo the nature of demand and forces. The leading players in Lite market are engaged in grand alliances to mop up resources for . ..,. intensive activities of development and registration and marketing of new crop protection molecules. branded pesticides, dealers’ loyalty lucrative schemes and seasonal price change. To strengthen the · tmg activities of Indian pesticide industry, these factors needs to be focused, which may lead to t lo Indian companies over other companies.